How should proxies of cognitive reserve be evaluated in a population of healthy older adults?. (17th October 2016) - Grotz, Catherine; Seron, Xavier; Van Wissen, Marie; Adam, Stéphane
ABSTRACT: Background: While some tools have been developed to estimate an individual's cognitive reserve (CR), no study has assessed the adequacy of the method used for assessing these CR proxy indicators. Therefore, we aimed to determine the most appropriate method to estimate CR by comparing two approaches: (1) the common assessment of CR proxies in the literature (e.g. years of education) and (2) the calculation of a comprehensive index based on most significant parameters used in the estimation of CR. Methods: Data on CR proxies (i.e. education, occupation, and leisure activities) were obtained in a sample of 204 older adults. Regression analyses were used to develop the two indices of CR (i.e. ICR-standard and ICR-detailed) and to determine which index best represented the level of one's CR. Results: The ICR-standard was calculated using a combination of the three most common measures of reserve in the literature: number of schooling years, complexity of the primary occupation, and amount of current participation in stimulating activities. The ICR-detailed was calculated using the most significant parameters (established in initial analyses) of CR: highest level of education combined with the number of training courses, last occupation, and amount of current participation in social and intellectual activities. The comparison of both indices showed that higher levels of ICR-standard and ICR-detailed were associated with a greater minimization of the effects of age on cognition. However, the ICR-detailed was more strongly associated to this minimization than the ICR-standard, suggesting that the ICR-detailed best reflect one's CR. Conclusions: This study is the first to show that it is of great importance to question methods measuring CR proxies in order to develop a clinical tool allowing a comprehensive and accurate estimation of CR.